# SOLUTION: Find an equation of the line containing the points (-3, 1) and (-1, 3).

Algebra ->  Algebra  -> Finance -> SOLUTION: Find an equation of the line containing the points (-3, 1) and (-1, 3).      Log On

 Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help! Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations!

 Algebra in Finance Solvers Lessons Answers archive Quiz In Depth

 Click here to see ALL problems on Finance Question 315602: Find an equation of the line containing the points (-3, 1) and (-1, 3).Found 3 solutions by jim_thompson5910, nyc_function, stanbon:Answer by jim_thompson5910(28503)   (Show Source): You can put this solution on YOUR website! First let's find the slope of the line through the points and Note: is the first point . So this means that and . Also, is the second point . So this means that and . Start with the slope formula. Plug in , , , and Subtract from to get Subtract from to get Reduce So the slope of the line that goes through the points and is Now let's use the point slope formula: Start with the point slope formula Plug in , , and Rewrite as Distribute Multiply Add 1 to both sides. Combine like terms. Simplify So the equation that goes through the points and is Notice how the graph of goes through the points and . So this visually verifies our answer. Graph of through the points and Answer by nyc_function(2733)   (Show Source): You can put this solution on YOUR website!We first find the slope. Let m = slope m = (3 - 1)/(-1 -(-3)) m = 2/(-1 + 3) m = 2/2 m = 1 The slope is 1. We now use the point-slope formula. y - y1 = m(x - x1) Pick one of the given points and the slope 1 to plug into the poitn-slope formula. y - 1 = 1(x - (-3)) y - 1 = 1(x + 3) y - 1 = x + 3 y = x + 3 + 1 y = x + 4 Done! Answer by stanbon(57240)   (Show Source): You can put this solution on YOUR website!Find an equation of the line containing the points (-3, 1) and (-1, 3). ----------------------- slope = (3-1)/(-1--3) = 2/2 = 1 -------------------------------------- Form: y = mx + b You know m = 1 and y = 1 when x = -3 ; solve for "b": 1 = 1*-3 + b b = 4 ---- Equation: y = x + 4 ================= Cheers, Stan H.